2022
DOI: 10.1088/1361-6595/aca0bb
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostics of a nanosecond atmospheric plasma jet. Electron and ro-vibrational excitation dynamics

Abstract: Atmospheric repetitive He discharge with 10 ns current peak width and 3 × 10 11  V s−1 voltage front rise working in jet geometry is studied. The first part of the study is devoted to electrical an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 91 publications
0
3
0
Order By: Relevance
“…Moreover, the shorter rise time also contributes to a faster propagation speed of the ionization wave [92]. Therefore, at relatively low pulse voltages, even if no runaway electrons are generated, a fast ionization wave may still occur, thereby shortening the gas breakdown time [93].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the shorter rise time also contributes to a faster propagation speed of the ionization wave [92]. Therefore, at relatively low pulse voltages, even if no runaway electrons are generated, a fast ionization wave may still occur, thereby shortening the gas breakdown time [93].…”
Section: Discussionmentioning
confidence: 99%
“…Dubinov [12] developed the non-linear theory of ion-acoustic waves in two-species isotropic collisionless plasma, derived the differential equation describing the profile of the ion concentration, and calculated profiles of the concentration in the periodic ion-acoustic wave and soliton. Britun et al [13] devoted to electrical and optical discharge characterization including voltage-current behavior, emission dynamics, as well as ro-vibrational dynamics of a nanosecond atmospheric plasma. They found that rather small air admixtures facilitate gas breakdown.…”
Section: Introductionmentioning
confidence: 99%
“…Britun et al. [13] devoted to electrical and optical discharge characterization including voltage‐current behavior, emission dynamics, as well as ro‐vibrational dynamics of a nanosecond atmospheric plasma. They found that rather small air admixtures facilitate gas breakdown.…”
Section: Introductionmentioning
confidence: 99%